Multimedia and Its Platforms for Archaeological Information Dissemination in Elmina - Adokpah, S. (My University, 2025)
This work investigates the role of multimedia and its platforms in disseminating archaeological research findings in Elmina, Ghana. This is intended to bridge the communication gap between researchers and local communities and diversify access to the results of archaeological and heritage investigations. Although multimedia technologies have transformed archaeology in recent years around the globe, with the attendant consequence of providing platforms to share archaeological discoveries with the general public, their impact has been limited in Ghana. This research thus sought to identify and document multimedia platforms used by the people of Elmina to assess the availability of information on Elmina cultural history. For the research, an Audio-visual document was uploaded to the multimedia platforms preferred by the people of Elmina, namely YouTube and TikTok. Multimodal ethnographic and other anthropological research strategies were also used to gather information. The results indicate that the people of Elmina preferred TikTok, Facebook, and other multimedia platforms to access archaeological research findings. These platforms are given preference above journal articles, books, chapters in books, seminars, and conferences. The audio-visual recommended by several respondents during the research is attached (https://youtu.be/kw1SDEphDD4?si=l7usLyrEUwKR_EX3).
MA. Museum and Heritage Studies
Keywords: multimedia; platforms; chaeological research; Elmina; Ghana